Analisis Faktor Determinan yang Mempengaruhi Pertumbuhan Ekonomi dan Implikasinya terhadap Penyerapan Tenaga Kerja - Munir, Abdul; Murti, Wahyu; Sutrisno, Sutrisno (Universitas Indraprasta PGRI, 2025)
The objective of this study is to ascertain the impact of inflation on economic growth in Jabodetabek, the extent to which technology influences economic growth in Jabodetabek, and the correlation between economic growth and labour absorption in Jabodetabek. The present study was conducted in Jakarta, Bogor, Depok, Tangerang, and Bekasi. The time period under consideration was from 2011 to 2020. The data was obtained using internet access from the Central Statistics Agency (https://www.bps.go.id). The population of this study is panel data on economic variables, namely economic growth, labour absorption, inflation, and technology. The sample consists of a segment of the population, specifically the island of Java, encompassing Jakarta, Bogor, Depok, Tangerang, and Bekasi, with economic variable data extending over the past decade from 2011 to 2020. The research model formulation employs multiple linear regression analysis and simple linear regression, specifically multiple linear regression. Inflation exerts a detrimental and substantial influence on economic growth. The island of Java is subject to inflation, the factors of which can be categorised as follows: firstly, the volatile food component, which is dominated by price shocks in the food group due to crop failures and inclement weather; secondly, developments in domestic and international food commodities; and thirdly, the conversion of agricultural land. The latter is also influenced by administered prices, which are prices regulated by the government, such as increases in fuel prices (BBM). The impact of technology on economic growth is both positive and significant. The role of technological innovation in driving economic growth is crucial and can have a significant impact. Technological innovation, particularly in terms of promotion, plays a pivotal role in the creation of new opportunities, the enhancement of efficiency, and the fostering of sustainable economic development.